The Role of Cultural Context in STEM Learning (Science, Technology, Engineering, and Mathematics): Perspective of Basic Education in Indonesia - Rofi’ah, Siti Hamidahtur; Abdillah, Fajar; Anisah, Ilyatul; Arif, Moh (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This study examines the integration of local cultural elements in STEM (Science, Technology, Engineering, and Mathematics) learning at the elementary school level in Jember Regency, Indonesia. The main objectives of this study were to identify relevant local cultural elements, understand teachers' and students' perceptions of culture-based STEM learning, and analyze challenges and opportunities in its implementation. The research method used was a qualitative approach with a case study, involving in-depth interviews, participant observation, and documentation analysis. The results showed that integrating local cultures, such as agricultural wisdom, art traditions, and the local environment, can increase the relevance and engagement of students in STEM learning. Teachers and students generally had positive perceptions of this approach, which was considered able to relate STEM concepts to their daily lives. However, challenges such as lack of teacher knowledge and limited resources need to be addressed to maximize the potential of cultural integration in STEM education. This study provides an important contribution to developing a more contextual and inclusive curriculum, as well as encouraging the preservation of local culture in the learning process.